Uporaba trdih prevlek PVD v strojništvu - možnosti in omejitve - Podgornik, Bojan (Strojniški vestnik, 2003)
A lot of new technologies, and thin films vith very good tribological properties, like diamond and diamond-like carbon coatings, were introduced in the past 2 to 3 decades. However, the use of hard, thin films in the field of machine elements is the exception rather than the rule. The main problem lies in the relatively high contact pressure and the very complex loading of the machine components, which demand a hard resistant surface and a tough core. It was found during many numerical and experimental analysis that in the case of hard, thin films the plastic deformation of the composite starts in the substrate. Therefore, the ability of the film to sustain the loading depends principally on the load-carrying capacity of the substrate. ...
Keywords: prevleke trde; trenje; obraba; nitriranje plazemsko; trde prevleke; tribološke lastnosti; jekla